Knowledge super corridors in Southeast Asia: seeing and doing from a critical lens - Han, Chun Kwong (IGI Global, 2012)
Developing countries in Asia are in the process of transitioning from a production economy to a knowledge-based economy. Various new knowledge and information communications technology mega-projects are being designed and executed at the international, national, state and industry levels to sustain competitiveness. The structures and processes by which these so-called “knowledge super corridors” are developed and implemented are complex economic-social-political decisions. The author develops an enhanced framework from critical theory, whereby the critical practice lens provides an iterative reflexive process, firstly by developing knowledge for understanding from structuration theory. Secondly, the author provides a critique of underpinning assumptions and presumptions whereby the constraining conditions of the status quo and emancipation become knowable and explicit, that is, knowledge for evaluation. Thirdly, the knowledge for action generated will enable the decision makers to re-create, re-define, re-design, re-imagine, re-invent and re-vision pragmatic, doable and implementable programs to transform a developing country into a k-economy. The author illustrates the value of the enhanced model using two case studies concerned with formulating and implementing a k-economy blueprint and developing a knowledge portal in emerging k-economies in Southeast Asia.